Exploring Women Empowerment in Kalidasa’s Sakuntala: The Role of Women in Shaping Identity - Neupane, Shrijana (GS WOW: Wisdom of Worthy Research Journal, 2024)
This research delves into Kalidasa's "Sakuntala," examining female empowerment and its role in identity formation within a patriarchal society. The purpose is to provide insights into feminist perspectives, gender roles, and the depiction of women in ancient literature. Using a qualitative approach, the study analyzes the representation of female characters and their negotiation of agency. Sakuntala, the resilient protagonist, confidently asserts her identity against patriarchal skepticism, showcasing strength and determination. Her journey, supported by Anasuya, Priyamvada, and mentored by Queen Gautami, emphasizes the significance of female solidarity and wisdom in navigating societal norms. Sakuntala's refusal to conform to patriarchal expectations until acknowledged by King Dushyanta highlights her autonomy. The research findings reveal the multifaceted nature of female empowerment in "Sakuntala," underscoring themes of resilience, solidarity, and self-assertion. By challenging male authority and societal norms, the female characters in Kalidasa's work illustrate the transformative power of empowerment. This study is valuable for scholars exploring ancient texts, feminist perspectives, and the complexities of identity formation, offering a deeper understanding of how female empowerment shapes women's identities and destinies in literature and society.